2017
DOI: 10.1016/j.tranon.2017.06.002
|View full text |Cite
|
Sign up to set email alerts
|

Systematic Analysis of the Expression of the Mitochondrial ATP Synthase (Complex V) Subunits in Clear Cell Renal Cell Carcinoma

Abstract: Mitochondrial dysfunction is common in cancer and the mitochondrial electron transport chain is often affected in carcinogenesis. To date, little is known about the expression of the ATP synthase subunits in clear cell renal cell carcinoma (ccRCC). The NextBio database was used to determine an expression profile of the ATP synthase subunits based on published microarray studies. We observed down-regulation of 23 out of 29 subunits of the ATP synthase. Differential expression was validated exemplarily for 12 ge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
46
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 55 publications
(48 citation statements)
references
References 46 publications
0
46
0
Order By: Relevance
“…In previous studies, we were able to show the dysregulation of specific subunits of the different respiratory chain complexes. Interestingly, a correlation of dysregulation and survival could be shown for some subunits . Taking up this idea, we carried out an extensive in silico analysis based on the TCGA data with a focus on the prognostic relevance.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In previous studies, we were able to show the dysregulation of specific subunits of the different respiratory chain complexes. Interestingly, a correlation of dysregulation and survival could be shown for some subunits . Taking up this idea, we carried out an extensive in silico analysis based on the TCGA data with a focus on the prognostic relevance.…”
Section: Discussionmentioning
confidence: 99%
“…In previous studies, it could be demonstrated that various subunits are downregulated in renal cell clear cell carcinoma. In addition, it has already been shown that the dysregulation of specific subunits is associated with a shortened survival . These findings prompted us to carry out a comprehensive expression analysis of the subunits, focusing on the prognostic impact.…”
Section: Introductionmentioning
confidence: 99%
“…HMGB3 promotes cell proliferation in colorectal cancer cells through regulation of MYC, where genes from same family have been linked to decreased MYC expression which is unique to proliferative subtypes of ovarian cancer (26). Lastly, ProteoMix also identifies hypo-methylation in two mitochondrial genes ATP5D and SPG7, speculatively linked to cancer through metabolic function (52).…”
Section: Resultsmentioning
confidence: 99%
“…NDUFA5 and NDUFA6 are two subunits of complex I, which play a direct role in complex I assembly [61,62]. ATP5F1, ATP5H, and ATP5PO are three subunits of complex V, which play a direct role in complex V assembly [63][64][65]. The downregulated expression of proteins involved in the oxidative phosphorylation process, including complex I and complex V, likely indicates that mitochondrial oxidative phosphorylation is impaired by PAD.…”
Section: Fatty Acid Beta Oxidationmentioning
confidence: 99%